Bowel recovery after intra vs extracorporeal anastomosis for oncologic laparoscopic right hemicolectomy within an ERAS protocol: A retrospective study. (1st June 2022) - Popeskou, S-G; Bernardi, L; Mongelli, F; Roesel, R; Cristaudi, A; Garofalo, F; Christoforidis, D
Abstract: Objective: Restoring bowel continuity after laparoscopic right hemicolectomy with an intra-corporeal (IC) rather than an extracorporeal (EC) ileocolic anastomosis, may offer advantages in post-operative recovery. The aim of this study was to compare bowel function recovery between these two techniques, in a context of complete mesocolic excision within an enhanced recovery after surgery (ERAS) protocol. Methods: All consecutive patients who underwent oncologic laparoscopic right hemicolectomy from January 2012 until February 2021 in our institution were included in the study. Data were gathered from the prospectively maintained official ERAS (EIAS) database and completed through our institution's electronic health records. The primary endpoint was Prolonged Postoperative Ileus (PPOI), defined as the need to insert a nasogastric tube, or refractory nausea VAS > 4, on or after the third postoperative day. Secondary endpoints were postoperative morbidity and length of hospital stay (LoS). Results: 122 patients met the inclusion criteria, 36 (30%) had IC, and 86 (70%) EC anastomosis. Baseline characteristics were similar. Operative time was longer in the IC group (197 min (176–223) vs. 160 min (140–189, p<0.001). There was no difference in post-operative morbidity between groups. PPOI occurred in 2 (5.6%) patients in the IC group vs. 10 (11.6%) in the EC group (p=0.306). Patients in the IC group had an earlier first passage of gas (1.5 days (1–2) vs. 2 days (1–3), p=0.035) and stool (2 days (2–4) vs. 3 days (2–4), p=0.029). Upon multivariate analysis, pain VAS scores at 24 h, age and complications Clavien-Dindo >III, but not the anastomotic technique were independent predictors of slower bowel function recovery. IC anastomosis was an independent predictor of lower pain VAS scores at 24 h (OR 0.341, 95%CI [0.151–0.767], p=0.009) and shorter LoS (OR 0.346, 95%CI [0.132–0.910], p=0.031). Conclusion: Although IC anastomosis was not significantly associated to lower rates of PPOI, it conferred advantages in terms of less post-operative pain, a trend for faster bowel recovery and shorter LoS at the expense of longer operating times.